Using Moral Foundations Theory to Enhance Multicultural Competency. Issue 2 (7th October 2018) - Romig, Charles A.; Holeman, Virginia T.; Sauerheber, Jill Duba
Abstract : Multicultural competency requires awareness of one's own values and possession of the knowledge and skills necessary to work ethically with clients who hold worldviews and values that may differ from the counselor. Recent cross‐cultural research on moral psychology provides a useful framework for categorizing values and understanding how clients prioritize competing values when making decisions. Six foundations of moral foundations theory are presented and matched to 6 ethical principles that are foundational to the ACA Code of Ethics (American Counseling Association, 2014 ). A case study illustrates how moral foundations theory can be applied in a culturally sensitive way.